2003
DOI: 10.1084/jem.20031440
|View full text |Cite
|
Sign up to set email alerts
|

CD40-deficient, Influenza-specific CD8 Memory T Cells Develop and Function Normally in a CD40-sufficient Environment

Abstract: Two models have been proposed to explain the requirement for CD40 signaling in CD8 T cell responses. The first model suggests that CD4 T cells activate antigen-presenting cells (APCs) through CD40 signaling (APC licensing). In turn, licensed APCs are able to prime naive CD8 T cells. The second model suggests that CD154-expressing CD4 T cells activate CD40-bearing CD8 T cells directly. Although the requirement for CD40 in APC licensing can be bypassed by inflammatory responses to pathogens that activate APCs di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
67
2

Year Published

2004
2004
2013
2013

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 87 publications
(77 citation statements)
references
References 23 publications
8
67
2
Order By: Relevance
“…Moreover, like CD40 signaling, also signaling via TLR4 and TLR9 led to CTL effector function and memory formation as mice rejected the initial tumor and were resistant to a subsequent rechallenge with tumor cells (data not shown). This was also evident in CD40 Ϫ/Ϫ mice after tumor eradication in response to treatment with CpG1826 ODN, indicating that, in contrast to previously published data (14), CD40 expression on CD8 ϩ T cells is not necessary for formation of CTL memory (40).…”
Section: Discussioncontrasting
confidence: 71%
“…Moreover, like CD40 signaling, also signaling via TLR4 and TLR9 led to CTL effector function and memory formation as mice rejected the initial tumor and were resistant to a subsequent rechallenge with tumor cells (data not shown). This was also evident in CD40 Ϫ/Ϫ mice after tumor eradication in response to treatment with CpG1826 ODN, indicating that, in contrast to previously published data (14), CD40 expression on CD8 ϩ T cells is not necessary for formation of CTL memory (40).…”
Section: Discussioncontrasting
confidence: 71%
“…However, some primary CD8 T cell responses to pathogens such as adenovirus (19), influenza virus (20), HSV-1 (21), and L. monocytogenes (22), are CD4 T cell help dependent. Because direct CD40-CD40L interaction between CD8 and CD4 T cells is not involved in these infections (34,35), it has been unclear why CD4 T cell help is needed in these settings. Our results presented here demonstrate that CD4 T cell help is also required for primary CD8 T cell response to VV infection in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…However, a number of reports have also demonstrated that CD40 is dispensable for the development of functional CD8 ϩ T cell memory upon immunization with virus-like particles or infection with other viruses or bacteria (31)(32)(33)(34).…”
Section: F Ollowing Exposure To Ag Naive Cd8mentioning
confidence: 99%